Yeast infection and diabetes mellitus among pregnant mother in Malaysia - Sopian, Iylia Liyana; Shahabudin, Sa’adiah; Ahmed, Mowaffaq Adam; Than, Leslie Thian Lung; Sandai, Doblin (Penerbit Universiti Sains Malaysia, 2016)
Background: Vaginal yeast infection refers to irritation of the vagina due to the presence of opportunistic yeast of the genus Candida (mostly Candida albicans). About 75% of women will have at least one episode of vaginal yeast infection during their lifetime. Several studies have shown that pregnancy and uncontrolled diabetes increase the infection risk. Reproductive hormone fluctuations during pregnancy and elevated glucose levels characteristic of diabetes provide the carbon needed for Candida overgrowth and infection. The goal of this study was to determine the prevalence of vaginal yeast infection among pregnant women with and without diabetes. Methods: This was a case-control study using cases reports from Kepala Batas Health Clinic,Penang State,Malaysia from 2006 to 2012. In total,740 pregnant ladies were chosen as sample of which 370 were diabetic and 370 were non-diabetic cases. Results: No relationship between diabetes and the occurrence of vaginal yeast infection in pregnant women was detected, and there was no significant association between infection and age group, race or education level. Conclusion: In conclusion, within radius of this study, vaginal yeast infection can occur randomly in pregnant women.